Representasi Kecerdasan Buatan (AI) Pada Iklan Sirup Marjan “Bangkitnya Calon Arang” Episode 1&2 Tahun 2025 Melalui Analisis Semiotika Charles Sanders Peirce - Anggraini Pramudita, Eka; Yayi Amanova , Felicciana (International Journal Labs, 2025)
Iklan not only functions as a marketing strategy, more than that advertising is also a forum for conveying social, cultural, and technological developments. The current issue of technological developments was expressed by Geoffrey Hinton, a computer scientist and artificial intelligence expert from Canada, who used the analogy of